 # { <mtable columnalign="left left" rowspacing=".2em" columnspacing="1em" displaystyle= vasorasy8 2022-07-10 Answered
$\left\{\begin{array}{l}{y}^{2}-3\ge 0\\ 16{y}^{4}-96{y}^{2}\ge 0\end{array}$
the solution for the first inequality is $y\le -\sqrt{3}$ or $y\ge \sqrt{3}$ and the solution for the second inequality is $-\sqrt{6}\le y\le \sqrt{6}$. Then for my result the solution for the system is
Then for my result the solution for the system is or $\sqrt{3}\le y\le \sqrt{6}$
You can still ask an expert for help

## Want to know more about Inequalities systems and graphs?

• Live experts 24/7
• Questions are typically answered in as fast as 30 minutes
• Personalized clear answers

Solve your problem for the price of one coffee

• Math expert for every subject
• Pay only if we can solve it Kroatujon3
$\left\{\begin{array}{l}{y}^{2}-3\ge 0\\ 16{y}^{4}-96{y}^{2}\ge 0\end{array}$
To satisfy condition 1
${y}^{2}-3\ge 0\phantom{\rule{thickmathspace}{0ex}}⟺\phantom{\rule{thickmathspace}{0ex}}{y}^{2}\ge 3\phantom{\rule{thickmathspace}{0ex}}⟺\phantom{\rule{thickmathspace}{0ex}}-\sqrt{3}\ge y$
To satisfy condition 2:
$16{y}^{4}-96{y}^{2}\ge 0\phantom{\rule{thickmathspace}{0ex}}⟺\phantom{\rule{thickmathspace}{0ex}}-\sqrt{6}\le y\le \sqrt{6}$
Then, to satisfy both conditions
$y\in \left(-\mathrm{\infty },-\sqrt{3}\right)\cap \left(\sqrt{3},+\mathrm{\infty }\right)\cap \left(-\sqrt{6},\sqrt{6}\right)=\left(-\sqrt{6},-\sqrt{3}\right)\cup \left(\sqrt{3},\sqrt{6}\right)$